2020
DOI: 10.1037/pla0000137
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sandplay therapy on the thalamus in the treatment of generalized anxiety disorder: A case report.

Abstract: Generalized anxiety disorder (GAD), a common, debilitating condition, involves psychological and physiological dysfunction. Sandplay therapy (SPT), a multisensory treatment modality, has been successfully used to reduce anxiety ratings for individuals suffering from GAD using the Hamilton Anxiety Rating Scale (HAM-A) and the General Anxiety-7 (GAD-7). Because GAD involves sensory processing alterations in the thalamus, which may also be implicated in SPT, it would be beneficial to accompany evaluation with a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…These results were accompanied by significant improvement in their symptoms of anxiety as measured by clinical assessments (HAM-A and GAD-7). The findings support the results of previous studies (Foo et al, 2017, 2020; Moon et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results were accompanied by significant improvement in their symptoms of anxiety as measured by clinical assessments (HAM-A and GAD-7). The findings support the results of previous studies (Foo et al, 2017, 2020; Moon et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…A complex pairing of the prefrontal and temporal regions (fronto-temporal network) showed the most noteworthy result, showing how sandplay enables the recovery and reprocessing of memories with an optimum amount of cognitive control. Another single-case neuroimaging study (Foo et al, 2020) showed improvement in the NAA/Cr ratio in the thalamus following SPT. However, SPT has not been studied with a focus on GAD patients experiencing CT, nor has a study been conducted that examines the effects of SPT on choline levels in the brain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study examining the intra-brain hemodynamics of a sandplayer during therapy, near-infrared spectrocopy (NIRS) signals from various prefrontal and superior temporal channels were found to be temporarily correlated ( Akimoto et al, 2018 ). Moreover, Foo et al (2020) assessed the metabolic changes in the bilateral thalami of an individual with generalized anxiety disorder. Using magnetic resonance spectroscopy, the N-acetyl aspartate to creatine (NAA/Cr) ratio (i.e., a measure of neuronal viability) was found to have improved after 18 sessions of ST.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging neuroimaging studies have found that sandplay therapy improved synchrony in frontotemporal networks of the brain, potentially facilitating the retrieval and reprocessing of memories with an optimal amount of cognitive control (Akimoto et al, 2018). Moreover, sandplay therapy effected symptom improvement in patients with generalized anxiety that was associated with improved brain functioning in the limbic system and prefrontal cortex (Foo et al, 2020; Foo & Pratiwi, 2021).…”
mentioning
confidence: 99%